Plant growth regulators application to enhance flowering and fruit production in GAC (Momordica cochinchinensis) - Hamidon, Azimah; Mohd Shah, Ramisah; Mohd Razali, Razifah; Lob, Suhaizan; Abdul Aziz, Fatma Azwani (Universiti Putra Malaysia, 2025)
Gac fruit (Momordica cochinchinensis) has garnered substantial interest due to its potential as a rich source of lycopene and β-carotene, prompting higher demand for large-scale production. However, the development of its female flowers is hindered by the dioecious nature of the gac plant, demanding manual pollination to enhance fruit yield. In addition, the female flower of the gac plant starts late, depending on environmental variables such as temperature, moisture, and photoperiod. Accelerating flowering onset and augmenting pollination could substantially amplify gac fruit production, provided a comprehensive comprehension of exogenous plant growth regulators is attained. Accordingly, the current study investigates the role of plant growth regulators at various concentrations in developing female flowers and fruit production in gac plants. A field planting experiment was conducted using a five-replication factorial randomized complete block design (RCBD). The combination treatments comprised two factors of interest, which were four different types of plant growth regulators (indole-3acetic acid [IAA], gibberellic acid [GA], benzyl adenine [BA], and maleic hydrazide [MH]) at four different concentration rates (0, 40, 80, and 120 ppm). Notably, Gac plants treated with MH at concentrations of 40 and 80 ppm exhibited significant performance in node and pistillate count, ovary diameter, early onset of first flower anthesis, and fruit yield. These findings underscore the potential of MH as a potent growth regulator for enhancing gac fruit production. Nonetheless, more research on agronomic practices, control environment modifications, and postharvest handling is required for the profitable production of the gac fruit.